Is part-time employment here to stay? Evidence from the Dutch labour force survey 1992 - 2005 - Nicole Bosch; Anja Deelen; Rob Euwals (Institute for the Study of Labor (IZA), 2008)
To balance work and family responsibilities, the Netherlands have chosen a unique model that combines a high female employment rate with a high part-time employment rate. The model is likely to be the result of (societal) preferences as the removal of institutional barriers, like lower marginal tax rates for partners and better childcare facilities, has not led to more working hours. It is, however, an open question whether the model is here to stay or whether younger generations of women will choose full-time jobs in the near future. We investigate the development of working hours over successive generations of women using the Dutch Labour Force Survey 1992-2005. We find evidence of an increasing propensity to work part-time over the successive generations, and a decreasing propensity to work full-time for the generations born after the early 1950s. Our results are in line with results of studies on social norms and attitudes as they find a similar pattern over the successive generations. It therefore seems likely that without changes in (societal) preferences the part-time employment model is indeed here to stay for some more time.
Keywords: J16; 330; Female labour supply; working hours; Teilzeitarbeit; Frauenerwerbstätigkeit; Work Life Balance; Niederlande